Accessibility compliance rates of consumer-oriented Canadian health care Web sites. - O'Grady, Laura (Medical informatics and the intrenet in medicine :an international journal of information processing in health care.)
Vast amounts of consumer-based health care information are widely available on the World Wide Web. However, for some this material is inaccessible due to reliance on specialized computer equipment or software knwon as assistive technology. These tools, designed for people with sensory, physical or learning disabilities, act as a median to interpret Web pages inaccessible ways. Unfortunately, many websites, including those with health-related content are not designed to accomodate this equipment. No research has yet been published examining the extent of this problem in Canadian consumer-oriented health care sites. The purpose of this study was to investigate the percentage of accessible consumer-based health care websites of Canadian origin. A listing of such sites was randomly sampled for study inclusion. Each was assessed for accessibility based on the World Wide Web Consortium (W3C) Web Accessibility Initiative (WAI) Web Content Accessibility Guidelines (WCAG) 1.0 using the validation software Bobby. The results indicated that only about 40% of pages investigated were free of errors in accordance with WCAG 1.0 Priority 1 level. Websites should be constructed in compliance with these standards to better accomodate those using assistive devices.